Carbon Dots for Future Prospects: Synthesis, Characterizations and Recent Applications: A Review (2019–2023) - Habtamu Fekadu Etefa; Aster Aberra Tessema; Francis Birhanu Dejene (C, 2024)
Carbon dots (CDs) have emerged as a promising class of carbon-based nanomaterials due to their unique properties and versatile applications. Carbon dots (CDs), also known as carbon quantum dots (CQDs) or graphene quantum dots (GQDs), are nanoscale carbon-based materials with dimensions typically less than 10 nanometers. They exhibit intriguing optical, electronic, and chemical properties, making them attractive for a wide range of applications, including sensing, imaging, catalysis, and energy conversion, among many others. Both bottom-up and top-down synthesis approaches are utilized for the synthesis of carbon dots, with each method impacting their physicochemical characteristics. Carbon dots can exhibit diverse structures, including amorphous, crystalline, or hybrid structures, depending on the synthesis method and precursor materials used. CDs have diverse chemical structures with modified oxygen, polymer-based, or amino groups on their surface. These structures influence their optical and electronic properties, such as their photoluminescence, bandgap, and charge carrier mobility, making them tunable for specific applications. Various characterization methods such as HRTEM, XPS, and optical analysis (PL, UV) are used to determine the structure of CDs. CDs are cutting-edge fluorescent nanomaterials with remarkable qualities such as biocompatibility, low toxicity, environmental friendliness, high water solubility, and photostability. They are easily adjustable in terms of their optical properties, making them highly versatile in various fields. CDs find applications in bio-imaging, nanomedicine, drug delivery, solar cells, photocatalysis, electrocatalysis, and other related areas. Carbon dots hold great promise in the field of solar cell technology due to their unique properties, including high photoluminescence, high carbon quantum yield (CQY), and excellent charge separation.